Informality and urbanisation in African contexts: analysing economic and social impacts - Aline Afonso (dir.) (Centro de Estudos Internacionais, 2015)
This book gathers five papers presented to the ECAS' 2013 proceedings. Following the theme of the Congress "African dynamics in a multipolar world", the challenge was to select among the 118 papers presented those which focused in the subjects of informality and space reconfiguration. The papers were selected from 4 panels: "Writing the world from another African metropolis: Luanda and the urban question", "Urbanisation and poverty in mining Africa", "Urban imaginaries in Africa" and "Managin...